Growth optimization of single-phase novel colloidal perovskite Cs3Bi2I9 nanocrystals and Cs3Bi2I9@SiO2 core–shell nanocomposites for bio-medical application. (31st August 2022) - Vedi, Santhana; Dheivasigamani, Thangaraju; Selvam, Govarthini Seerangan; Kawakami, Takashi; Rajeswaran, Narmadha; Rajendran, Selvakumar; Muthukaruppan, Alagar; AlFaify, S.; Shkir, Mohd.
Abstract : Lead-free Cs3 Bi2 I9 material is chosen to eliminate its single-phase synthesis difficulty and implementing Cs3 Bi2 I9 @SiO2 towards bioimaging applications. Cytotoxicity of Cs3 Bi2 I9 @SiO2 was demonstrated using MTT assay in L929 fibroblast cells. Abstract : Lead-free halide perovskites have gained attention in recent years as viable materials with more distinctive characteristics than conventional semiconductor materials. Lead-free Cs3 Bi2 I9 colloidal perovskite nanocrystal is chosen to eliminate its single-phase synthesis difficulty and implement the material in bioimaging applications. Nanostructured Cs3 Bi2 I9 perovskite composites were coated with a thin coating of SiO2 by an in situ tetraethyl orthosilicate/(3-aminopropyl)trimethoxysilane injection growth method to enhance their stability in aqueous medium and biocompatibility. Single-phase novel Cs3 Bi2 I9 colloidal perovskite nanocrystal synthesis was successfully developed and optimized by adopting different synthetic conditions with varied experimental parameters. Characterization studies, including X-ray diffractometry and transmission electron microscopy, confirm the hexagonal structure of Cs3 Bi2 I9 crystals and their cubic morphology. A broad emission peak in the red region was captured for pure and composite perovskite under different excitation wavelengths and was observed using a UV-visible spectrophotometer. Bioimaging of Cs3 Bi2 I9 @SiO2 composites incorporated with L929 cells was conducted using an inverted fluorescence microscope under blue and green excitation. The results obtained from bioimaging studies indicated that the Cs3 Bi2 I9 @SiO2 nanocomposites entered the cell field and exhibited an emission under excitation. The non-toxic behavior of the synthesized Cs3 Bi2 I9 @SiO2 composites was demonstrated using MTT cytotoxicity assay in L929 fibroblast mouse cells, showing better cell compatibility.